A context-aware dispatcher for the Internet of Things: The case of electric power distribution systems. (May 2016) - Amin, Shaimaa A.A.; Ali-Eldin, Amr; Ali, Hesham Arafat
Abstract : Graphical abstract: Highlights: Detailed explanation of an automatic dispatcher, its components and functions. Framework structure is based on context-awareness integration. with IOT middleware Framework tested in electrical distribution systems as a case study. High progress in the system performance in terms of cost, time and effort. Acceleration in faults repairing and increased user satisfaction. Abstract: Automating actions based on collected context from Internet of Things (IOT)-controlled systems is one of the most important requirements of IOT systems; this paper seeks to satisfy this requirement by offering a context-aware service framework on top of IOT controlled systems. The fault management process in electric power distribution networks is taken here as a case study and used for implementing our proposed framework. We discuss the different aspects that need to be covered in such a framework and its components. The obtained results from simulating and testing the framework show a significant improvement in the task management process compared to the traditional approach.